Ganhando na loteria e temendo perder o prêmio: a experiência de famílias rurais ao ter a mãe/esposa sobrevivente de câncer de mama - Mistura, Claudelí (2014)
With the transformations of the brazilian new rural , the family is going through adaptations in its everyday life and reformulating sociocultural and interactional scenarios. These changes can be perceived in the familiar arrangements and functioning. For the family which lives in the rural area, this is the place where their interactions and experiences happen. The movement that the rural family performs, in the moment they have a family member sick with cancer, enlarges and reflects the sociocultural life of these people. The diagnosis of breast cancer in a mother/wife can consist in a challenge for the family that has to face the illness, get along with the demands of the treatment and the uncertainty of the prognosis. Finishing, successfully, the treatment and having the mother/wife considered as cured means a new step in the family life. In this sense, the goals of this study are to understand the experience of the rural families as they have the mother/wife as a survivor of breast cancer as well as to elaborate a Theoretical Model representative of this familiar experience. It is a qualitative and descriptive research, guided by the theoretical apparatus of the Data Grounded Theory (DGT). The participants were 41 members from six rural families that live in the micro region of Marau/RS/Brasil, which had the mother/wife as survivor of breast cancer. The data were produced through open interviews and building of the familiar genome. The study was approved by the Ethical Committee of Federal University of Santa Maria under the number 13105413.2.0000.5346. The data analysis was carried out in accordance with the Constant Comparative Method from DGT, which resulted in the elaboration of the theoretical model representative of rural families experiences by having mother/wife survivor of breast cancer, defined by the central categories RECOGNIZING THEMSELVES AS A VICTORIOUS FAMILY and (NOT) BELIVING IN THE SURVIVING OF BREAST CANCER and the organization of eight categories which are intertwine and constitute the experience: Reliving experiences of the illness (1); Trying to make the treatment as soon as possible (2); Keeping the diagnosis in secret (3); Having to deal with contradictory feelings (4); Having repercussion in the family with the experience (5); Defining the illness by cancer (6); Recurring to the spiritual and religious beliefs (7); and Waiting for the five years (8). We conclude that the experience is a process which occurs in a time line traveled by the families even before living the illness of the mother/wife in the familiar nucleus. The experience of the rural families as they have the mother/wife survivor of breast cancer can be described as resulting of a constant, interactive and integrated moving where the family recognize themselves as victorious, who win in the lottery by having the mother/wife considered as cured, but that, by the fear of relapsing, they are afraid of losing the prize and live feelings of ambiguity for (not)believing in the cancer cure.